Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1073/pnas.1115057109
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and developmental requirements for the Prader–Willi imprinting center

Abstract: Imprinted gene expression associated with Prader-Willi syndrome (PWS) and Angelman syndrome (AS) is controlled by two imprinting centers (ICs), the PWS-IC and the AS-IC. The PWS-IC operates in cis to activate transcription of genes that are expressed exclusively from the paternal allele. We have created a conditional allele of the PWS-IC to investigate its developmental activity. Deletion of the paternal PWS-IC in the embryo before implantation abolishes expression of the paternal-only genes in the neonatal br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Targeted mutations in mice confirm that the PWS-IC functions somatically, activates paternal gene expression, and is necessary to silence the paternal Ube3a allele (10)(11)(12)(13)(14). However, the absence of a conserved AS-SRO sequence in mice has stymied functional investigations into this element of the imprinting center.…”
mentioning
confidence: 99%
“…Targeted mutations in mice confirm that the PWS-IC functions somatically, activates paternal gene expression, and is necessary to silence the paternal Ube3a allele (10)(11)(12)(13)(14). However, the absence of a conserved AS-SRO sequence in mice has stymied functional investigations into this element of the imprinting center.…”
mentioning
confidence: 99%
“…Other interesting questions that remain to be answered are whether TADs arise from gDMR-directed interactions or whether TADs support imprinted domains independent of the gDMR. The Snrpn ICR has been shown to be critical for maintenance of imprinted expression of genes within the domain in the preimplantation embryo, yet is dispensable for maintaining Peg12, Mkrn3, Magel2, and Ndn imprinted expression in the neonatal brain (Dubose et al 2012), supporting the latter. In this case, it is possible that at the Snrpn imprinted domain, TADs supported by LADs and LOCKs are sufficient to maintain paternal-specific expression in the neonatal brain.…”
Section: Resultsmentioning
confidence: 97%
“…Depletion of the Ube3a-as lncRNA via very large and small Snrpn/Ube3a-as promoter deletions or through truncation of the Ube3a-as transcript results in reactivation of the paternally-silenced Ube3a allele in neurons differentiated from ESCs and in the mouse brain in a dose-dependent manner (Bressler et al 2001;Chamberlain and Brannan 2001;Kantor et al 2004;Dubose et al 2011;Dubose et al 2012;Meng et al 2012Meng et al , 2013. Recent evidence suggests that Ube3a-as disrupts Ube3a transcription through a mechanism of transcriptional collision (Meng et al 2013).…”
Section: Tads At Imprinted Domainsmentioning
confidence: 97%
“…Moreover, a recent report demonstrated that an enhancer associated with the T-cell-specific CD4 gene is required for initiating activation of the gene locus in undifferentiated cells that do not express the target gene, but is no longer required in differentiated cells that express the CD4 gene [80]. Likewise, DuBose et al [81] demonstrated that deletion of the SNRPN imprinted control region during early embryonic development causes imprinting defects of the associated genes; however, deletion of this element in adult brain cells has no effect on imprinted gene expression. These studies support a previous finding from the Schaffner laboratory showing that the B-cell-specific IgH enhancer is only transiently required for setting up the active state of the target gene [82].…”
Section: Poised Enhancers During Cellular Differentiationmentioning
confidence: 99%